Telepathos: Medium Cool Romanticism - Langan, Celeste (Romanticism on the Net, 2006)
AbstractThis essay argues for the critical value of situating Romantic poetry—particularly as it’s theorized by Wordsworth and Scott—as a “medium” between the two extremes that often shape accounts of media history: the “primary orality” of Walter Ong and the “techno-informatic vanishing point” of aesthetics recently described by Alan Liu in The Laws of Cool. I propose that Sir Walter Scott’s story, “My Aunt Margaret’s Mirror,” offers a “supernatural” or occulted account of how literature operates as a kind of telepathic medium, enabling readers to be “affected by absent things as if they were present.” But it offers at the same time, in its almost anachronistic play with the concept of “resolution” as a feature of the televisual screen, an account of all perception—both “immediate” and mediated—as a process of discretization and resynthesis that works remarkably like Wordsworth’s “digital” theory of meter.